2022
DOI: 10.3390/cancers14030574
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use and Breast Cancer Risk According to Molecular Subtypes Status: A Systematic Review and Meta-Analysis of Case-Control Studies

Abstract: We conducted a systematic review and meta-analysis to investigate the effect of oral contraceptives (OCs) on risk of breast cancer (BrCa) by status of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). We searched the MEDLINE (PubMed), Embase and the Cochrane Library database and bibliographies of pertinent articles published up to 2020. Therein, we identified nineteen eligible case-control studies which provided data by breast cancer subtypes: ER-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Recently a meta-analysis pointed out that HC-induced risk was tied to breast cancer receptor status, where increased risks were noted for women with ER negative and triplet-negative breast cancer. 28 In contrast, a reduced risk from HC use was noted in ER positive cancers. 28 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently a meta-analysis pointed out that HC-induced risk was tied to breast cancer receptor status, where increased risks were noted for women with ER negative and triplet-negative breast cancer. 28 In contrast, a reduced risk from HC use was noted in ER positive cancers. 28 …”
Section: Discussionmentioning
confidence: 98%
“…However, important information from the Cancer Register such as receptor status, stage and pathology would have given a more complete picture of the associations. 28 Final limitations of this study is that we followed the women for a relatively short period of time, and we only included women up to 34 years of age at the start of the study. As progestogen-only methods are the most common contraceptives in women 35–50 years of age, and as the absolute risk of breast cancer increases at this age, we may have underestimated the risk of using progestogen-only methods.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous meta-analysis of the effect of OC use on the risk of breast cancer was conducted for the general population [ 26 ]. We included 19 studies evaluating the impact of OCs on the risk of specific molecular subtypes of breast cancer (a total of 246,152 individuals, including 31,250 cases and 214,902 as a control).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our meta-analysis based on the general population indicated that each use of OCs significantly increased the risk of TNBC: OR = 1.37, 95% CI; 1.13 to 1.67, p = 0.002, as well as ER−BC: OR = 1.20, 95% CI: 1.03 to 1.40, p = 0.019. The summary meta-analysis also showed a significant reduction in the risk of ER+BC: OR = 0.92, 95% CI: 0.86 to 0.99, p = 0.026, and a slight reduction in the risk of HER2+BC: OR = 0.95, 95% CI; 0.79 to 1.14, p = 0.561 after OC taking [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation